Execution of Fiduciary Guarantee at Consumer Finance Institutions - W, Sundaru Guntur; Prihadyatama, Ecbla; Susanto, Fredy (West Science Law and Human Rights, 2024)
Motor vehicles are a staple need today, so that the existence of consumer finance companies is very much needed by the community, In addition, the high level of need for consumptive goods and the limited ability or purchasing power of most people to buy in cash make consumer finance institutions so much in demand by the community, so that consumer finance institutions (consumer finance) is quite active in supporting the business world in Indonesia, both for new motorcycles and for used motorcycle units as well as financing furniture and electronic goods. Consumer financing activities are carried out by providing installment payment options in accordance with the consumer's ability and long term. Problems arise when installment payments are delayed or even to the act of deliberately transferring the vehicle to another party without the approval of the financing institution. When this happens, the financing institution will finally look for its vehicle rather than looking for a debtor who will definitely not pay installments anymore, for that a third party called a debt collector appears who is invited to work together. The pros and cons of using third-party services are what make the author analyze in this study, because often the use of third-party services will also cause new problems.